Public Policy and Change Reactions from Citizens in Nigeria (Journal of Management and Social Sciences, 2022)
Public Policy usually attracts reactions from the people in the society which may be positive or negative depending on the way such a policy is viewed by individuals, groups and society in general. The paper focused on change reactions from the citizens arising from some government policies. It was against this backdrop that the paper examined some policies embarked upon by government and the various change reactions arising therefrom. Using secondary data analysis, the paper examined some policy changes that have been embarked upon by successive administrations since 1999, and the reactions to these changes, with particular focus on President Jonathan’s Administration as well as President Muhammadu Buhari’s Administration and his Party, All Progressive Congress (APC), whose slogan is “Change”. The three policies examined revealed that most of the reactions were negative. The paper, therefore, concluded that the citizens’ negative reactions were a result of government’s failure to interact with the people that the policies would affect before coming up with them. It was suggested that policy process should not be mutually exclusive to the formulators and implementers of public policy alone. Rather, the beneficiaries of public policies should be carried along through thorough enlightenment and accommodation of inputs and contributions from them.  Keywords    Policy, change, citizens, governance